Experimental infection of laying hens with Salmonella enterica serovar gallinarum - De Oliveira, Gláucia Helaine [UNESP]; Berchieri, Angelo [UNESP] (My University, 2005)
Experimental infections were set up in commercial laying birds, comprising a white relatively resistant line and a red susceptible line infecting with Salmonella enterica serovar Gallinarum. The major findings were that in susceptible birds clinical disease occurred in a dose-dependent manner. Faecal excretion occurred in susceptible birds almost up to death but also occurred in the more resistant line and in birds, which were convalescing. Removal of birds, which had died from the disease, from the environment, reduced the resultant mortality/morbidity and may be regarded as a useful measure for control.
Keywords: Contact infection; Laying hens; Salmonella Gallinarum